Consumer attitude towards green products: revisiting the profile of green consumers using segmentation approach. Issue 5 (30th March 2021) - Mehta, Pooja; Chahal, Harpreet Singh
Abstract : Purpose: Over the last few decades, there has been a substantial increase in environmentally conscious consumers' willingness to switch their preferences from mainstream products to green products. Hence, it becomes essential for academicians and marketers to understand the notion, attributes and a comprehensive profile of green consumers. Since consumer attitude towards green products is not widely studied in developing countries, the present study aims at exploring the profile of green consumers in India (Punjab State) based on the same in the Indian context. Design/methodology/approach: The study used the survey method, and a sample of 400 respondents was selected from the Punjab State of India. Initially, principal component analysis was employed to reduce the dimensions. Following this, cluster analysis was applied to segment consumer market in distinctive segments. Results of cluster analysis were validated with discriminant analysis and finally, differences amongst the segments of green and non-green consumers were examined to build on the profile of green consumers. Findings: The study segmented the consumer market based on consumer attitude towards green products. Results of the study revealed four distinct segments. "Dynamic Green", the largest cluster, presents truly green consumers who exhibit a positive attitude towards green products. Finally, the study highlighted the attitudinal profile of green and non-green consumers and differences amongst the segments were explained. Research limitations/implications: Similar study should be conducted in other developing/developed countries. Furthermore, cross-cultural studies can be undertaken to contrast consumer attitude towards green products. The study may also be extended to probe the connection between consumers' attitude and actual behaviour towards green products. Originality/value: The study examined the role of consumer attitude towards green products in identifying the distinct segment of green consumers and determining different configurations of consumer characteristics to build on the profile of green consumers.